Penerapan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) dalam Meningkatkan Hasil Belajar Biologi Siswa Kelas VIII - Samputri, Salma; Surati, Surati (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
Increasing student learning outcomes cannot be separated from the teaching and learning process, one of which is the use of learning models. The learning model used in the teaching and learning process is expected to make it easier for students to accept and understand the material presented. This research is classroom action research with the stages of implementation including: planning, implementing, acting, reflecting, and evaluating repeatedly. This research was carried out at SMP IT Albiruni with the research subjects being class VIII students with a total of 40 students who were taught directly by the researcher. This research was conducted in November-December 2020 at SMP IT Albiruni, taking place in the odd semester of the 2020/2021 academic year. The results showed that the Team Assisted Individualization (TAI) type of cooperative learning model could improve biology learning activities on the concept of the human movement sistem for eighth grade students of SMP IT Albiruni. Keywords: Movement Sistem, Cooperative, Learning Strategy, Albiruni